Outcomes for human immunodeficiency virus-1-infected infants in the United kingdom and Republic of Ireland in the era of effective antiretroviral therapy. - Doerholt, K; Duong, T; Tookey, P; Butler, K; Lyall, H; Sharland, M; Novelli, V; Riordan, A; Dunn, D; Walker, A; Gibb, D (2006)
BACKGROUND: There are few data about disease progression and response to antiretroviral therapy (ART) in vertically HIV-infected infants in the era of effective therapy. DESIGN: Cohort study. METHODS: We examined progression to acquired immunodeficiency syndrome (AIDS) and death over calendar time for infants reported to the National Study of HIV in Pregnancy and Childhood in the United Kingdom/Ireland. The use of ART and CD4 and HIV-1 RNA responses were assessed in a subset in the Collaborative HIV Pediatric Study. RESULTS: Among 481 infants, mortality was lower in those born after 1997 (HR 0.30; P < 0.001), with no significant change in progression to AIDS. Of 174 infants born since 1997 in the Collaborative HIV Pediatric Study, 41 (24%) were followed from birth, 77 (44%) presented pre-AIDS and 56 (32%) presented with AIDS. Of 125 (72%) children on 3- or 4-drug ART by the age of 2 years, 59% had HIV-1 RNA <400 at 12 months; median CD4 percentage increased from 24% to 35%. Among 41 infants followed from birth, 12 progressed to AIDS (5 while ART naive) and 3 died; 1 of 10 infants initiating ART before 3 months of age progressed clinically. CONCLUSION: Mortality in HIV-infected infants is significantly lower in the era of effective ART, but symptomatic disease rates remain high. Infrequent clinic attendance and poor compliance with cotrimoxazole prophylaxis and/or ART in infants born to diagnosed HIV-infected women and late presentation of infants identified after birth appear to be major contributors. Poor virologic response to ART during infancy is of concern because of increased likelihood of early development of resistance.